Students’ Perception On The Use Of “Grammarly” In Thesis Writing At Nahdlatul Ulama University - Elis Susiana; Nizarrahmadi Nizarrahmadi; Alvina Yolanda (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. This study aims to find out how students’ perception use Grammarly in the process of preparing their thesis at Nahdlatul Ulama University. The research method used is a qualitative method. The participants in this study were eight-semester students who were in the process of preparing their thesis. The participants in this study were eight people. How to collect data using the interview method and the Google form, the Google form was distributed to 6 students and 2 students conducted direct interviews to explain more deeply about students’ perceptions of using grammarly in writing thesis. This research is also to find out what are the strengths and weaknesses of grammatical applications. The results of this study indicate that students have positive responses and opinions toward the use of Grammarly in their thesis writing. Students found Grammarly very helpful in the process of checking grammar, spelling, punctuation, and capitalization. The feedback that is easy to understand and its many features make students use the Grammarly application a lot. The weakness of Grammarly is that its feature cannot detect what tenses are used in a paragraph. Students also have to pay if they want to get complete premium features